Considerations on the type specimens and type locality of Pyrrhura roseifrons (Gray, 1859) (Psittacidae) - Costa, Thiago V. V.; Joseph, Leo; Silveira, Luís Fábio (Zootaxa, 2016)
The Rose-fronted Parakeet Pyrrhura roseifrons (Gray, 1859) is a poorly known species that occurs in lowland forest of western Amazonia, from eastern Peru to western Brazil and northern Bolivia (Collar 1997; Forshaw 2010). Like many Pyrrhura species, it is mostly green, and has a pale auricular patch, red tail and belly, but presents a bright red head, distinct from any other close relatives within the genus. It was long considered a subspecies of P. picta (Statius Miller, 1776) (Arndt 1983; Arndt 1996; Collar 1997; Juniper & Parr, 1998) and only recently has its specific rank been restored (Joseph 2000, 2002; Ribas et al. 2006) and accepted in the literature (Dickinson & Remsen 2013; del Hoyo & Collar 2014; Remsen et al. 2015).